Enhancing Secondary School Admissions through Effective Management Models: Insights from Primary School Transitions - Dian; Nailan, Akhmaliah Siti; Sariah, Dedeh; Wahyuni, Femy Sri (Universitas Pendidikan Ganesha, 2024)
The management of new student admissions plays a crucial role in supporting the realization of quality education. Therefore, its implementation must be carried out in a well-structured and systematic manner. This study aims to analyze the description and reinforcement of new student admission management in secondary schools originating from primary schools. The study employed a descriptive method with a qualitative approach. Data collection techniques included interviews, observations, and relevant literature reviews. The data obtained were analyzed using thematic analysis to identify patterns and key findings related to the new student admission management process. The findings reveal that the management of new student admissions from primary to secondary schools adopts the Planning, Programming, Budgeting System (PPBS) model, which encompasses three main steps: planning, programming, and budgeting. The results also indicate that the number of new students from primary schools has significantly increased over the past five years, peaking at 184 new students. The implementation of the PPBS model in new student admission management has proven effective in increasing student enrollment and strengthening the administrative system for admissions.The study concludes that the use of the PPBS model can enhance the management process of new student admissions in secondary schools, ensuring a more efficient and effective admission system.